On Endogenous Economic Regulation - Stanley Reiter (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
This paper presents a model in which in each of a succession of time periods the State and the private economy interact to determine rules under which the private agents will operate in the next period, and rules and resources that constrain interventions of the State in the next period. The set of State institutions, called regulators, that are the instruments of State intervention is endogenously determined in each period. The model is a multiperiod game consisting of two phases. The first is a (noncooperative) game played by private economic agents in each period, the rules for which are given by the regulators in the preceding period. The second phase is political. In each period the private agents acting politically determine the legal and budgetary constraints under which the regulators will operate in the next period, and thereby determine the noncooperative game to be played in the next period. Formal entities in the model allow a wide variety of regulatory instruments and transfer payments to be represented.
Keywords: 330